Development of the Android-Based Educational Game Media “Perjalanan Si Maya” as a Formative Assessment to Improve Critical Thinking Skills and Interest in Learning Science for Elementary School Students - Devi Falamila Putri Anggraeni; Wahono Widodo; Zainul Arifin Imam Supardi (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2023)
Objective: This research aims to develop an android-based educational game media,